Investigation of Selected Heavy Metals Level in Top Soils Around Ajaokuta Steel Company, North Central Nigeria - S. Olatunji, Olatunde; Osibanjo, Oladele (Asian Journal of Chemistry, 2014)
The concentration of selected heavy metals in top soils around Ajaokuta Steel Company was investigated in order to evaluate the environmental status level of the metals. Top soil samples were randomly collected around Ajaokuta Steel Company between 2003 and 2005. The samples were sorted; air dried, pulverized to < 2 mm grain size and digested using standard methods. The soil digest solutions were quantified for Cd, Cr, Mn, Ni, Cu, Zn and Pb using flame atomic absorption spectrometry. The mean concentrations (mg/kg) of the heavy metals were; Zn, 56.30 ± 11.94; Cu, 42.90 ± 5.84; Pb, 15.62 ± 3.06; Cr, 14.33 ± 2.38; Ni, 11.48 ± 2.13; Mn, 6.53 ± 1.68; and Cd, 0.13 ± 0.16, with soil concentration distribution in the order Zn > Cu > Pb > Cr > Ni > Mn > Cd. The soils were slightly acidic with mean pH 6.54 ± 0.67 and mean organic carbon levels of 2.03 ± 0.72 %. Significant correlation (p < 0.05) exists between the concentration of heavy metals in soils and organic carbon levels, with correlation coefficient for Mn; g = 0.51 and Cr; g = 0.63. The transport/availability of metals in soils is strongly influenced by pH and organic carbon levels, and this forms the basis of their fixation with plant growth nutrients. The retention of metals in soil organic matter proceeds by complexation. The stability of the metal-organic carbon complexes depends on the organic carbon type, nature of the complex formed and the degree of stearic effect.